2020
DOI: 10.3390/su12187262
|View full text |Cite
|
Sign up to set email alerts
|

FIViz: Forensics Investigation through Visualization for Malware in Internet of Things

Abstract: Adoption of the Internet of Things for the realization of smart cities in various domains has been pushed by the advancements in Information Communication and Technology. Transportation, power delivery, environmental monitoring, and medical applications are among the front runners when it comes to leveraging the benefits of IoT for improving services through modern decision support systems. Though with the enormous usage of the Internet of Medical Things, security and privacy become intrinsic issues, thus adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It is observed that each study incorporated more than one forensic visualization technique. Furthermore, most of the related studies demonstrated the selection of techniques based on data types, for example in [64], [57], [61], and [66]. This further indicates that different data types may require different visualization techniques.…”
Section: B Research Trends Of Forensic Visualization For Forensic Ana...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is observed that each study incorporated more than one forensic visualization technique. Furthermore, most of the related studies demonstrated the selection of techniques based on data types, for example in [64], [57], [61], and [66]. This further indicates that different data types may require different visualization techniques.…”
Section: B Research Trends Of Forensic Visualization For Forensic Ana...mentioning
confidence: 99%
“…The utility of the tool was evaluated through questions derived from forensic analysis goals: what cyber incident occurred, who was involved in the incident, and where, when, and how the incident occurred. Also applying timeline graph visualization, [66] presented a visualization-based approach to support malware investigations on the Internet of Things environment. This study applied the data mining method to preprocess DLL files and assign weights to represent malicious and benign files.…”
Section: A Role Of Visualization For Forensic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These attacks not only threaten the integrity and confidentiality of IoMT devices, but they are also capable of shutting down any network server through DDoS attacks [61,62]. This can forcefully open a backdoor to a given medical system or device [63,64]. Besides, exploiting the security gap can also lead to unauthorized access to medical records, disclosure, IoMT devices, or deletion of patient's information [20].…”
Section: Malware Attackmentioning
confidence: 99%
“…Security devices are becoming vulnerable to privacy-threatening attacks launched by malicious users, and because of these attacks, it is difficult to completely control the widely distributed IoT devices. For controlling the data leakage from IoT devices, an authorized access mechanism is needed to protect sensitive and valuable information [4].…”
Section: Introductionmentioning
confidence: 99%